Game Theory and the Law: The "Legal-Rules-Acceptability Theorem" {A Rational for Non-Compliance with Legal Rules) - Flores Borda, Guillermo (2011)
Until now, legal science has lacked of a formal explanation forthe biggestand mostobvious legal problem: "non-compliance with legal rules': This papel defies the common sense idea that non-compliance with legal rules is a psychological issue by providing the first formal game-theoretic explanation regarding how people decide wthether to comply with a specific legalrule, and provides a solution that any policy maker can apply in arder to reduce legal non-compliance rates.